MicroRNAs in Muscle: Characterizing the Powerlifter Phenotype - D'Souza, Randall F.; Bjørnsen, Thomas; Zeng, Nina; Aasen, Kirsten M. M.; Raastad, Truls; Cameron-Smith, David; Mitchell, Cameron J. (Frontiers in Physiology, 2017)
Powerlifters are the epitome of muscular adaptation and are able to generate extreme forces. The molecular mechanisms underpinning the significant capacity for force generation and hypertrophy are not fully elucidated. MicroRNAs (miRs) are short non-coding RNA sequences that control gene expression via promotion of transcript breakdown and/or translational inhibition. Differences in miR expression at rest may partially account for phenotypic differences in muscle mass and function between powerlifters and untrained age-matched controls. Muscle biopsies were obtained from m. vastus lateralis of 15 national level powerlifters (25.1 ± 5.8 years) and 13 untrained controls (24.1 ± 2.0 years). The powerlifters were stronger than the controls (isokinetic knee extension at 600/s: 307.8 ± 51.6 Nm vs. 211.9 ± 41.9 Nm, respectively P <0.001), and also had larger muscle fibers (type I CSA 9122 ± 1238 µm2 vs. 4511 ± 798 µm2 p<0.001 and type II CSA 11100 ± 1656 µm2 vs. 5468 ± 1477 µm2 p<0.001). Of the 17 miRs species analysed, 12 were differently expressed (p<0.05) between groups with 7 being more abundant in powerlifters and five having lower expression. Established transcriptionally regulated miR downstream gene targets involved in muscle mass regulation, including myostatin and MyoD, were also differentially expressed between groups. Correlation analysis demonstrates of abundance eight miRs were correlated to phenotype including peak strength, fiber size, satellite cell abundance and fiber type regardless of grouping. The unique miR expression profiles between groups allow for categorisation of individuals as either powerlifter or healthy controls based on a five miRs signature (miR-126, -23b, -16, -23a, 15a) with considerable accuracy (100%). Thus, this unique miR expression may be important to the characterization of the powerlifter phenotype.